Analisis Kualitas Pelayanan pada Ritel Tradisional dengan Metode Customer Satisfaction Index (CSI) dan Retail Service Quality Scale (RSQS) - Dadang, Ali; Isharyani, Muriani Emelda; Tosungku, La Ode Ahmad Safar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study was conducted to assess the service quality of UMKM Amplang Bontang Store by applying the Customer Satisfaction Index (CSI) and the Retail Service Quality Scale (RSQS). The results indicate that the overall service quality is relatively good, as reflected in a CSI score of 74%, signifying that customers are fairly satisfied with the store’s services. Among the dimensions, social interaction achieved the highest CSI score (83%), while the policy dimension recorded the lowest (63%). Further analysis using the RSQS method identified that the policy dimension has the most significant negative gap (-1.0). Specifically, attribute KB4 (-1.91) emerged as the lowest-performing attribute, making the policy dimension particularly KB4 the primary focus for service improvement.